Analysis of Factors Affecting Household Income of Waste Bank Customers in Medan City - Harahap, Rifqah; Rahmadana, Muhammad Fitri; Nugrahadi, Eko Wahyu (Advances in Social Sciences Research Journal, 2019)
Income is one indicator to measure the welfare of a person or society. In this study, the household income of waste bank customers is classified as low and medium income. Many factors cause a person has low-income; one crucial aspect is the type of work, the outpouring of work time and others. The purpose of this study was to analyze and determine the effect of the outpouring of work time, waste sale prices, age of workers, number of household members, work experience and radius of waste collection toward the household income of customers of waste banks in Medan City. The data used in this study are primary data with a total sample of 120 customers with the sampling technique of respondents conducted by cluster random sampling and data collection techniques using questionnaires. The data analysis model used is multiple linear regression. The results of this study indicate that the outpouring of work, the selling price of waste, and the number of household members have a positive and significant effect on the household income of the waste bank customers. The age of the worker has a positive and insignificant effect on the household income of the waste bank customers. Whereas work experience and radius of waste collection have a negative and insignificant effect on the household income of waste bank customers.